Minoxidil: New Areas of Opportunity! - Luis Octavio Victoria García; Morelos Adolfo García Sánchez; Rafael Martínez Sanciprián; Miranda Llama Luna; Mariana Carolina Zúñiga García; Luis Alberto González Valdez; Marco Antonio Hernández Hernández; Oscar Gregorio Ramírez Gamboa; Karla Lizeth Martínez González; Melba Michelle Romero Ovando; Zarah Georgina Pérez Diosdado (British Journal of Healthcare and Medical Research, 2026)
Introduction: Minoxidil is a compound chemically synthesized in the laboratory, it underwent clinical trials in hypertensive patients in 1961. Objective: To carry out art history based on an exhaustive search of the national and international medical literature on its therapeutic use of minoxidil in humans. Discussion: the topical use of routine minoxidil for the treatment of multiple hair disorders. 2% and 5% minoxidil continue to be the approved treatments, with the most efficient being 5%, with an expected phase of loss, even under treatment. Another use that has been reported for minoxidil is that used together with phototherapy, it is the most common treatment for vitiligo; A novel bioengineering approach to improve local delivery in the skin. The hydrogels are highly mechanically robust micro-needle patches with heights of 600 or 800 μm with sufficient mechanical strength to penetrate human skin. Minoxidil has been used in yellow nail syndrome, a rare disorder characterized by a triad of thickened yellow nails, primary lymphedema, and chronic respiratory manifestations. It has been determined as a treatment as an antihypertensive drug and has been studied since 2008, stating that minoxidil should be used together with β-blockers and diuretics. Conclusions: Minoxidil has demonstrated beneficial effects in androgenic alopecia, scarring and alopecia areata; however, it has been shown that there are other areas of therapeutic opportunities in other diseases, due to their already known pharmacological actions, evoking the option of new research protocols